Alcoholic Chlorhexidine or Alcoholic Iodine Skin Antisepsis (ACAISA): protocol for cluster randomised controlled trial of surgical skin preparation for the prevention of superficial wound complications in prosthetic hip and knee replacement surgery. Issue 5 (15th May 2014) - Peel, T N; Cheng, A C; Buising, K L; Dowsey, M M; Choong, P F M
Abstract : Introduction: Wound complications following arthroplasty are associated with significant impact on the patient and healthcare system. Skin cleansing prior to surgical incision is a simple and effective method to prevent wound complications however, the question of which agent is superior for surgical skin antisepsis is unresolved. Methods and analysis: This cluster randomised controlled trial aims to compare the incidence of superficial wound complications in patients undergoing elective prosthetic hip or knee replacement surgery receiving surgical skin antisepsis with either: 0.5% chlorhexidine gluconate (CHG) in 70% alcohol or 10% povidone in 70% alcohol. The trial will be conducted at an Australian tertiary, university affiliated hospital over a 3-year period involving 750 participants. Participants will be drawn from the surgical waiting list. Consent for this study will be 'opt-out' consent. On a given day, all eligible participants will have skin preparation either with 0.5% chlorhexidine in 70% alcohol or 10% povidone iodine in 70% alcohol. The primary outcome is superficial wound complications (comprised of superficial incisional surgical site infections (SSI) and/or prolonged wound ooze) in the first 30 days following prosthetic joint replacement surgery. Secondary outcomes will include the incidence of wound complications according to the joint replaced, assessment of the causative agents of SSI and cost-effectiveness analysis. The primary analysis is an intention-to-treat analysis including all participants who undergo randomisation and will be performed at the individual level taking into account the clustering effect. Ethics and dissemination: The study design and protocol was reviewed and approved by the St Vincent's Hospital Human Research Ethics Committee (HREC-A 016/14 10/3/2014). Study findings will be disseminated in the printed media, and learned forums. A written lay summary will be available to study participants on request. Trial registration number: The trial has been registered with the Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12614000177651.